El representante aduanero - La Noire Núñez, José Antonio (2023)
This article develops concepts regarding the change in the regulations established in Peru on the certification, accreditation and authorization process of the customs representative, as well as the requirements that the customs agent must meet customs to be authorized as an economic operator to register his representative. Likewise, the author reflects on the existing legal basis, thinking about the doubts and questions that international business students and future applicants for the customs representative program may have about both figures of Peruvian foreign trade, since it must be clear that the Customs agent is the operator authorized by the Customs Administration, while the customs representative is the person accredited by the Administration for the purpose of representing one or more operators, depending on the exclusivity of the provision of their services.